Evaluation method for the authenticity of recycled particles of used carbon-containing magnesia refractory materials
By quantifying the weight percentage of magnesium sand particles in the carbon-containing magnesium-containing regenerated particles, the problem of lack of effective evaluation methods for correcting effect in the prior art is solved, and a scientific and reasonable evaluation and improvement of the quality of regenerated particles is achieved.
Patent Information
- Application Number
- CN202410982654.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-07-22
AI Technical Summary
The prior art lacks an effective evaluation method for capacity correction effect, resulting in different quality of carbon-magnesium-containing regenerated particles after use, and excessive capacity correction leads to high energy consumption and high processing costs.
A method for evaluating the return degree of carbon-containing magnesium-containing regenerated particles after use is proposed. The return degree is quantified by the percentage of the weight of magnesium sand particles occupying the entire weight of regenerated particles, and objectively evaluated based on the calculation results.
It has achieved an accurate and efficient, scientific and reasonable evaluation of the degree and quality level of carbon-containing magnesium-containing regenerated particles after use, provided specific evaluation standards, and improved the utilization value and recycling rate of recycled materials.
Smart Images

Figure CN119198435B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for evaluating the trueness of recycled particles of used carbon-containing magnesium refractory materials, and belongs to the technical field of recycled material processing evaluation for recycling of solid waste refractory materials. Background Art
[0002] In recent years, in order to enhance market competitiveness, save production costs, reduce solid waste of refractory materials and the resulting environmental pollution and land occupation, more and more refractory practitioners have made the recycling of used refractory materials a research focus, and the degree of attention has continued to deepen. Carbon-containing magnesia refractory materials are one of the most common refractory materials in the steel industry. They are widely used in the lining construction of metallurgical kilns such as steelmaking converters, electric furnaces, and ladles, as well as in functional components such as air-permeable bricks, steel outlets, slides, and nozzles. The annual domestic consumption is about 1.2 million tons. If roughly calculated based on a 30% residual rate of offline production, nearly 360,000 tons of used carbon-containing magnesia refractory materials will be generated each year, and the resulting solid waste volume is huge.
[0003] As we all know, after sorting and regeneration, the recycled particles of used carbon-containing magnesium refractory materials present a structural morphology of magnesium sand particles coated with a graphite carbon layer under the binding effect of the binding carbon layer (resin residue), forming the phenomenon of recycled pseudo particles widely criticized in the industry. The existence of pseudo particles will seriously affect the physical and chemical indicators and key service performance of the recycled products, and greatly restrict the batch recycling of recycled refractory materials. In response to the current pseudo particle problem, scientific and technological workers have carried out a lot of technical research and proposed many treatment processes and solutions to eliminate the pseudo particle effect: (1) Mechanical stripping method: Use rolling or rotary impact to apply mechanical force to the carbon coating layer to achieve separation and thinning of the outer coating; (2) Oxidation burning method: The used recycled particles are subjected to high-temperature oxidation roasting at a temperature above 800°C, and the binding carbon layer and graphite carbon layer are completely oxidized by chemical methods. (3) All-round volume correction process: The integrated coordinated treatment process of selective low-temperature oxidation roasting (chemical method), low-temperature medium cold shock (physical method), and high-efficiency variable speed and variable direction grinding (mechanical method) can achieve the best volume correction effect, approach the true morphology of magnesia particles to the greatest extent, and greatly improve the utilization value of recycled materials.
[0004] Although the above-mentioned relatively mature correction processing technology and technology for dealing with the false particle effect are available, there is a lack of effective correction effect evaluation methods. In actual operation, most practitioners still use experience and traditional visual observation to measure, and there is no unified specific quantitative evaluation method and standard. This leads to uneven quality of carbon-containing magnesium regeneration particles after use, and there are also many problems such as high energy consumption and high processing costs caused by excessive correction. Therefore, the invention of a scientific, reasonable, objective and accurate false particle correction effect evaluation method has become one of the most difficult issues that need to be solved in the field of post-use carbon-containing magnesium regeneration treatment. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for evaluating the authenticity of regenerated particles of used carbon-containing magnesia refractory materials. The method combines the morphological characteristics of used carbon-containing magnesia regenerated pseudo particles, and defines the authenticity as the percentage of the weight of magnesia sand particles in the total weight of used carbon-containing magnesia regenerated particles. The degree of approximation between the used carbon-containing magnesia regenerated particles and the original particles is quantified, and an objective evaluation is made on the correction effect based on the calculation results. The method can accurately, efficiently, scientifically and reasonably evaluate the authenticity and quality level of used carbon-containing magnesia regenerated particles.
[0006] To solve the above problems, the specific technical solution of the present invention is as follows: A method for evaluating the trueness of regenerated particles of used carbon-containing magnesia refractory materials, comprising the following steps:
[0007] The used carbon-containing magnesium regeneration particles include magnesium sand particles and an outer graphite carbon layer; the return to trueness can be quantified as the percentage of the weight of magnesium sand particles to the weight of the entire used carbon-containing magnesium regeneration particles, and the calculation formula is as follows:
[0008]
[0009] Wherein, W1 is the mass of magnesia particles in the used carbon-containing magnesium regeneration particles, W2 is the mass of graphite carbon layer, and P is the return to trueness for evaluating the reprocessing process;
[0010] Evaluation criteria: When P < 95%, the return to trueness index of the used carbon-containing magnesium regeneration particles is unqualified, and further deep re-capacity treatment or scrapping is required; if 95% ≤ P < 97%, the return to trueness can be judged as qualified, but the used carbon-containing magnesium regeneration particles should be downgraded or appropriately re-capacity treatment should be carried out; if P ≥ 97%, the return to trueness index is excellent,
[0011] The used carbon-containing magnesium regenerated particles can be used directly.
[0012] There are two sources of the spent carbon-containing magnesium regeneration particles. One is self-production and self-collection. The chemical composition of the original raw materials is completely known, and samples are stored for reference. Chemical analysis can be performed at any time. The chemical analysis evaluation method can be used to evaluate the return of truth, that is, the magnesium oxide content W in the spent carbon-containing magnesium regeneration particles is detected by chemical analysis method. MgO and carbon content W C , and combined with the magnesium oxide content F in the original magnesia raw material MgO , Carbon content F in the original graphite raw material C , we can get their equivalent relationship with W1 and W2, and substitute them into formula (1) to get the calculation formula of return to truth P based on chemical analysis evaluation method; the other is to purchase from the market, the original raw material information is unknown, and there is no sample for reference. It is necessary to first prepare the reference particles by manual fine grinding of the used carbon-containing magnesium regenerated particles. For this, the volume density detection method should be used to evaluate the return to truth, that is, the volume density of the used carbon-containing magnesium regenerated particles and the reference particles is tested, and the equivalent relationship with W1 and W2 is derived and calculated through the volume density value, and substituted into formula (1) to get the calculation formula of return to truth P based on the volume density detection method.
[0013] The chemical analysis method includes the following steps:
[0014] Step 1, random sampling: randomly select the used carbon-containing magnesium regeneration particles with a particle size of ≥0.5 mm, with a total amount of 500 g to obtain a preliminary sample;
[0015] Step 2, sample grouping: Use mesh sieves with apertures of 1 mm and 3 mm to manually screen and group the preliminary selected samples extracted in step 1 to obtain sample group I with particle size <1 mm, sample group II with particle size 1 mm≤<3 mm, and sample group III with particle size ≥3 mm. Use weighing equipment to weigh each sample group and calculate its percentage G1, G2, and G3 of the total weight of the preliminary selected samples;
[0016] Step 3: Group testing: Use existing testing methods to measure the magnesium oxide content W of sample group I, sample group II and sample group III obtained in step 2. M g O and carbon content W C ;
[0017] Step 4: Calculate the return truth degree P by group n : Query and obtain the original raw material information of the used carbon-containing magnesium regeneration particles, and calculate the magnesium oxide content F in the original magnesium sand raw material. M g O and the carbon content F in the original graphite raw material C The magnesium oxide content W of each sample group measured in step 3 M g O and carbon content W CSubstituting them into formula (4.1) for calculation, we can calculate the return to truth P1, P2, P3 of sample group I, sample group II and sample group III respectively;
[0018]
[0019] Where P n is the return to truth of sample group n, is the magnesium oxide content of sample group n, is the carbon content of sample group n.
[0020] Step 5, comprehensive evaluation: Substitute the weight percentage of each sample group calculated in step 2 and the true return P1, P2, P3 of each sample group obtained in step 4 into formula (5) to calculate the comprehensive true return P;
[0021] P=G1·P1+G2·P2+G3·P3 Formula (5)
[0022] In the formula, G1, G2, and G3 are the percentages of each sample group in the total amount of the preliminary selected samples, and their total amount should be 100%, that is,
[0023] G1+G2+G3=1.
[0024] The bulk density test method includes the following steps:
[0025] Step 1, preparation of reference particles: first, a sieve is used to randomly screen a number of coarse particles with a particle size of ≥4mm from the used carbon-containing magnesium recycled particles, and a number of round and full particles are selected from them to obtain reference particle rough selection materials; then, 320# or higher sandpaper is used to manually grind and polish the surface of the reference particle rough selection materials until the entire surface of the particles emits a magnesium sand crystal luster, and the reference particles are obtained; the weight of the obtained reference particles is 300g;
[0026] Step 2, sample selection: randomly select a number of used carbon-containing magnesium regeneration particles, and screen them with a sieve with an aperture of 3 mm, and take the sieve to obtain a sample; the weight of the selected sample is 300g;
[0027] Step 3: Perform volume density tests on the reference particles and samples respectively to obtain the volume density D of the reference particles. 真 and the bulk density D0 of the sample;
[0028] Step 4: Calculate the return to truth P: D0 and D 真 Substitute into formula (10) to calculate the return to truth P;
[0029]
[0030] The present invention has the following advantages:
[0031] 1. Strong operability: This application provides a specific return to truth calculation formula, and the calculation process is very simple, and proposes a specific test method for the data required for each item in the formula. By quantifying and measuring the return to truth, the operability of the evaluation process is effectively enhanced.
[0032] 2. The test and calculation methods have good reproducibility and parallelism, and the evaluation results are objective and accurate: This evaluation method always focuses on the appearance and morphology of the carbon-containing magnesium regeneration particles and the change rules of its chemical and physical indicators during the thinning of the coating layer. The derived return to truth calculation formula is closely in line with reality. After multiple parallel tests, it was found that the standard deviation of the multiple calculation results of the return to truth was extremely small, showing good reproducibility. At the same time, by designing multiple groups of corresponding tests, it was found that the return to truth calculation results can accurately evaluate the capacity correction effect.
[0033] 3. Specific evaluation standards are proposed: the calculated return to truth is classified into different levels according to different numerical ranges, thus forming a specific and easy-to-operate evaluation standard system. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the pseudo-particle morphology of the carbon-containing magnesium regenerated particles after use. DETAILED DESCRIPTION
[0035] From the attached Figure 1 It can be seen that the carbon-containing magnesium regenerated particles after use are actually formed by the graphite carbon layer (mass W2) coating the magnesium sand particles (mass W1) under the bonding effect of the binding carbon layer (mass W3) to form a kind of magnesium sand pseudo-particle morphology. Since the binding carbon layer is a thin carbonized layer formed after the phenolic resin wets the magnesium sand particles and is carbonized at high temperature, W3 is very small, and the binding carbon changes to graphitization at high temperature, it has a very small effect on the carbon content detection of the entire carbon-containing magnesium regenerated particles after use. It can usually be attributed to the graphite carbon layer for calculation, which can be verified from multiple precise chemical analysis experiments and formula reverse calculations. Therefore, in order to ensure that the calculation and evaluation process is simple and easy, the above-mentioned pseudo-particle model of carbon-containing magnesium regenerated particles after use can be simplified to a double-layer structure in which the graphite carbon layer (mass W2) directly coats the magnesium sand particles (mass W1). Based on this simplified model and according to the definition in the previous article, the return to trueness can be quantified as the percentage of the weight of the magnesium sand particles to the weight of the entire carbon-containing magnesium regenerated particles after use, and the calculation formula is as follows:
[0036]
[0037] Wherein, W1 is the mass of the magnesia particles in the carbon-containing magnesium regeneration particles after use, and W2 is the mass of the graphite carbon layer.
[0038] From formula (1), we can know that the calculation of return to trueness must first calculate W1 and W2 according to the information of the used carbon-containing magnesium regenerated particles and their original raw materials. The information of the original raw materials usually depends on the recycling source of the used carbon-containing magnesium refractory materials:
[0039] First, the used carbon-containing magnesium refractory material is self-produced and collected, and its original raw material information (including the main component content, etc.) is completely known, or its original raw material has samples for reference, and chemical analysis can be performed at any time. In this case, the present application uses a chemical analysis method to derive and calculate W1 and W2 using the test values of MgO and C content in the used carbon-containing magnesium regenerated particles and the main component content value of the original raw materials. Substituting them into formula (1) can derive a return to truth calculation formula based on chemical composition analysis, and proposes a chemical analysis evaluation method.
[0040] Second, the used carbon-containing magnesium refractory materials are purchased from the market, and all the original raw material information is unknown in most cases, and there is no sample to check. For this type of used carbon-containing magnesium regenerated particles, this application proposes to prepare reference particles by manual fine grinding, and respectively test the volume density of used carbon-containing magnesium regenerated particles and reference particles. The volume density values of the two are used to derive and calculate W1 and W2, and substitute them into formula (1) to derive the return-to-true degree calculation formula based on the volume density of true and false particles, and propose a volume density detection method.
[0041] Next, the working principles and implementation steps of the chemical analysis evaluation method and the volume density detection method will be explained in detail:
[0042] (I) Chemical analysis and evaluation method: The general idea is to first use chemical analysis methods to detect the MgO and C content values in the used carbon-containing magnesium regeneration particles, and then substitute them together with the MgO and C content values in the original raw materials into the specified formula to calculate the return to trueness. According to the calculated return to trueness and evaluation criteria, a reasonable evaluation is made on the volume correction effect of the used carbon-containing magnesium regeneration particles.
[0043] (1) Calculation formula of return to truth based on chemical analysis evaluation method
[0044] If the recycled carbon-containing magnesium particles are self-produced and self-collected, the original raw material information is completely known, that is, the magnesium oxide content F in the original magnesia raw material used. MgO and the carbon content F in the original graphite raw material C It is completely known that the magnesium oxide content (W) in the carbon-containing magnesium regeneration particles after use can be measured by chemical analysis. MgO ) and carbon content (W C ), then there is the following equivalent relationship between the above chemical contents:
[0045]
[0046]
[0047] Dividing equation (2) by equation (3) yields Substituting it into formula (1), we can get:
[0048]
[0049] It can be seen that after mastering the main component content F of the original raw material of carbon-containing magnesia refractory MgO 、F C In this case, or there is a sample for inspection and detection MgO 、F C If the conditions are met, it is only necessary to use chemical testing to test the magnesium oxide content (W MgO ) and carbon content (W C ), the degree of return to truth P can be quickly calculated according to formula (4), thereby achieving the purpose of efficiently evaluating the effect of the correction. From formula (4), it can be seen that if the carbon content W of the carbon-containing magnesium regeneration particles is used in the chemical analysis C =0, the return to trueness is 100%, which means that after the carbon-containing magnesium regeneration particles are corrected, the carbon coating layer disappears completely and the true particle morphology is completely restored.
[0050] (2) Specific implementation steps of chemical analysis evaluation method
[0051] For used carbon-containing magnesia refractory materials from self-production or other sources where the original raw material information can be fully mastered, the calculation and evaluation of the trueness of the used carbon-containing magnesia recycled particles shall preferably adopt the chemical analysis evaluation method. The specific implementation steps are as follows:
[0052] Step 1: Random sampling. After the correction treatment, according to the procedures and methods specified in the relevant standards of GB / T17617 "Rules for Sampling and Inspection of Refractory Raw Materials", a total of 500g of the used carbon-containing magnesium regenerated particles (particle size ≥ 0.5mm) are randomly sampled to obtain the preliminary sample.
[0053] Step 2: Sample grouping. Use mesh sieves with apertures of 1mm and 3mm to manually screen and group the preliminary samples extracted in step 1 to obtain sample group I (particle size <1mm), sample group II (1mm≤particle size <3mm), and sample group III (≥3mm). Use weighing equipment to weigh each sample group and calculate its percentage G1, G2, and G3 of the total weight of the preliminary samples. Since the volume correction effect of the carbon-containing magnesium regenerated particles after use may be related to the particle size, and most of them are used in the production of regenerated refractory materials in the form of particle size classification, this application will group the samples by particle size to achieve the expected goals of multi-level detection, comprehensive evaluation, comprehensive grasp, and classified processing.
[0054] Step 3: Group testing. According to GB / T 5069.11 "Chemical analysis method for magnesium and magnesium-aluminum (aluminum-magnesium) refractories - Determination of calcium oxide and magnesium oxide content by complexometric titration", GB / T 13245 "Chemical analysis method for carbon-containing refractories - Determination of total carbon content by combustion weight method" or any other method that can accurately determine the content of magnesium oxide and carbon, the magnesium oxide content (W) of sample group I, sample group II, and sample group III obtained in step 2 is determined respectively. M g O ) and carbon content (W C ).
[0055] Step 4: Calculate the return truth degree P by group n Query and obtain the original raw material information of the used carbon-containing magnesium regeneration particles, and calculate the magnesium oxide content F in the magnesium sand. M g O and graphite carbon content F C The magnesium oxide content (W) of each sample group measured in step 3 M g O ) and carbon content (W C ) are substituted into formula (4) to calculate the return to truth P1, P2, and P3 of sample group I, sample group II, and sample group III, respectively, namely:
[0056]
[0057] Where P n is the return to truth of sample group n, is the magnesium oxide content of sample group n, is the carbon content of sample group n.
[0058] Step 5: Comprehensive evaluation. Substitute the weight percentage of each sample group calculated in step 2 and the various fidelity P1, P2, and P3 obtained in step 4 into the following formula to calculate the comprehensive fidelity P:
[0059] P=G1·P1+G2·P2+G3·P3 Formula (5)
[0060] In the formula, G1, G2, and G3 are the percentages of each sample group in the total amount of the preliminary selected samples, and their total amount should be 100%, that is, G1+G2+G3=1
[0061] It should be noted that the national standard without a year number quoted in the above steps usually refers to the latest version of the national standard.
[0062] Comprehensive evaluation criteria: If the calculated comprehensive return to trueness P is less than 95%, the return to trueness index is unqualified and the entire particle size range needs to be processed again or scrapped; if 95% ≤ P < 97%, the return to trueness can be concluded to be qualified, but in order to maximize the quality of the used carbon-containing magnesium recycled materials and increase their recycling rate, the screening system can be used to selectively downgrade or re-correct the corresponding particle size materials with lower return to trueness in the three sample groups; if P ≥ 97%, an assessment conclusion can be made that the return to trueness index is excellent, and the entire particle size range of the used carbon-containing magnesium recycled materials can be directly used.
[0063] (ii) Bulk density test method: The general idea is to first use manual fine grinding to restore and prepare reference particles, that is, the original magnesia particles of the used carbon-containing magnesium refractory material, and use the same method to respectively test the volume density values of the used carbon-containing magnesium regenerated particles and the reference particles, and then substitute them into the specified formula to calculate the return to trueness. According to the calculated return to trueness and evaluation criteria, an objective evaluation is made on the volume correction effect of the used carbon-containing magnesium regenerated particles.
[0064] (1) Calculation formula for trueness based on volume density detection method
[0065] In the simplified double-layer model of the magnesia particles and the graphite carbon coating layer of the used carbon-containing magnesium regeneration particles, the bulk density and volume of the magnesia particles are recorded as D 真 、V 真 , the volume density and volume of the graphite coating are denoted as D 包 、V 包 The volume density and volume of the entire used carbon-containing magnesium regeneration particles are recorded as D0 and V0, then W1 = D 真 ·V 真 , W2=D 包 ·V 包 , and the weight of the entire regenerated particles (W1+W2) can be calculated as follows:
[0066] W1+W2=D 真 ·V 真 +D 包 ·V 包 =D0·(V 真 +V 包 ) Formula (6)
[0067] Substituting equation (6) and the expressions of W1 and W2 into (1), the return to truth can be expressed as:
[0068]
[0069] In addition, V can also be derived from formula (6): 真 With V 包 Has the following relationship:
[0070]
[0071] Substituting formula (8) into formula (7), formula (7) can be transformed into:
[0072]
[0073] Since the graphite carbon layer is mainly composed of flaky graphite, it is a ridge material that is difficult to sinter due to its high melting point and good chemical stability. It is generally believed that its volume density does not change with temperature within the use temperature range of carbon-containing magnesia refractory materials, and is not affected by the forming process of magnesia carbon bricks. Therefore, the volume density of the graphite carbon layer is constant as 2.25g / cm according to the average volume density of flaky graphite. 3 , that is, D 包 =2.25g / cm 3 Substituting it into formula (9) can obtain the return truth calculation formula based on the volume density detection method:
[0074]
[0075] Where D0 is the volume density of the regenerated carbon-containing magnesium particles after use, D 真 It is the volume density of the reference particles. It can be seen from the formula that when the volume density of the regenerated carbon-containing magnesium particles is equal to the density of the original magnesium sand particles, the return to trueness is 100%. After the volume correction treatment, the original magnesium sand particles and the carbon coating layer are completely separated, and the volume correction effect is optimal.
[0076] (2) Specific implementation steps of the bulk density test method
[0077] For those used carbon-containing magnesia refractory materials purchased from the market or other materials whose original raw material information cannot be mastered, the calculation and evaluation of the regenerated particle return trueness cannot be carried out by chemical analysis and evaluation. The bulk density test method can be used uniformly. The specific implementation steps are as follows:
[0078] Step 1: Preparation of reference particles. First, use a sieve to randomly screen a number of coarse particles (≥4mm) from the used carbon-containing magnesium regeneration particles, and select a number of particles with a round and full appearance as reference particle rough selection materials. Then use 320# or above sandpaper to manually grind and polish the surface of the reference particle rough selection material until the entire surface of the particle emits the luster of magnesium sand crystals, and then the reference particles are obtained. Furthermore, in order to ensure the normal progress of subsequent steps, the reference particles prepared in this step are required to reach 300g.
[0079] Step 2: Sample selection. According to the procedures and methods specified in the relevant standards of GB / T17617 "Rules for Sampling and Inspection of Refractory Raw Materials", a number of carbon-containing magnesium regeneration particles are randomly selected and screened with a sieve with an aperture of 3mm, and the sieved material is taken to obtain a sample. Furthermore, in order to ensure the normal progress of the subsequent steps, the weight of the sample selected in this step is 300g.
[0080] Step 3: Bulk density test. According to GB / T2999 "Test method for bulk density of refractory particles", the bulk density of the reference particles and samples was tested to obtain D 真 、D0.
[0081] Step 4: Calculate the return to truth P. D0 and D 真 Substitute into formula (10) to calculate the return to truth P.
[0082] Step 5: Evaluation of return to trueness: Based on the return to trueness calculated in step 4 and the following evaluation criteria, the correction effect of the used carbon-containing magnesium regenerated particles is evaluated.
[0083] The return to trueness evaluation standard is: if P < 95%, the return to trueness index is unqualified, and the used carbon-containing magnesium regenerated particles need to be further subjected to deep re-capacity rectification or scrapped; if 95% ≤ P < 97%, the return to trueness can be judged as qualified, but the used carbon-containing magnesium regenerated particles should be downgraded or appropriately re-capacity rectified; if P ≥ 97%, the return to trueness index is excellent, and the used carbon-containing magnesium regenerated particles can be directly used as magnesium raw materials.
[0084] The following will combine the application scenarios of false particle correction and return to trueness evaluation of used carbon-containing magnesium refractory materials from different sources, and explain the technical solution of the present invention in detail through specific examples. However, it is worth noting that these examples are only the best implementation schemes for a specific application scenario and do not limit the scope of the present invention.
[0085] Example 1 Evaluation of the Authenticity of Self-produced and Self-harvested Used Carbon-containing Magnesium Regenerated Particles after Volume Correction Treatment
[0086] The object of this embodiment is a used carbon-containing magnesium refractory material derived from self-production and collection, and is prepared from used carbon-containing magnesium regenerated particles (particle size ≥ 0.5 mm) through recycling, sorting, crushing, screening, and volume correction processes. All the original raw materials of the regenerated material have samples in reserve, and their relevant chemical composition information can be checked at any time. Therefore, in order to quantify the volume correction effect of the object, guide the formulation of volume correction process parameters and evaluate the quality of regenerated particles, this embodiment is suitable for using chemical analysis and evaluation methods to evaluate its return to truth, and the specific implementation steps are as follows:
[0087] Step 1: Random sampling. After the correction treatment, according to the procedures and methods specified in GB / T17617-2018 "Rules for Sampling and Inspection of Refractory Raw Materials", a total of 500g of the used carbon-containing magnesium regenerated particles (particle size ≥ 0.5mm) are randomly sampled to obtain the preliminary sample.
[0088] Step 2: Sample grouping. The preliminary samples extracted in step 1 were manually screened and grouped using mesh sieves with apertures of 1mm and 3mm to obtain sample group I (particle size <1mm), sample group II (1mm≤particle size <3mm), and sample group III (≥3mm). Each sample group was weighed using a weighing device, and the weights were 105g, 212g, and 183g, respectively. The percentage of each sample group in the total weight of the preliminary samples was then calculated. Since the volume correction effect of carbon-containing magnesium regeneration and reduction particles may be related to the particle size, and most of them are used in the production of regenerated refractory materials in the form of particle size classification, this application will group the samples by particle size, and expects to achieve multi-level detection, comprehensive evaluation, comprehensive understanding, and classified processing.
[0089] Step 3: Group testing. According to GB / T 5069.11 "Chemical analysis methods for magnesium and magnesium-aluminum (aluminum-magnesium) refractories - Determination of calcium oxide and magnesium oxide by complexometric titration", the magnesium oxide contents of sample group I, sample group II, and sample group III obtained in step 2 were measured to be W respectively. 1 MgO =95.21%, W 2 MgO =95.65%, W 3 MgO =97.35%. According to GB / T 13245 “Chemical analysis methods for carbon-containing refractory materials - Combustion weight method for determination of total carbon content”, the carbon contents of sample group I, sample group II and sample group III are W 1 C =3.02%, W 2 C =2.68%, W 3 C =1.04%.
[0090] Step 4: Calculate the return truth degree P by group n By querying the original raw material information of the carbon-containing magnesium regeneration particles used in this embodiment, it can be known that the magnesium oxide content F in the magnesia sand is MgO =97.68%, flake graphite raw material carbon content F C =94.15%, and compared them with the magnesium oxide content (W MgO ) and carbon content (W C) are substituted into formula (4.1) to calculate the return to truth P1, P2, and P3 of sample group I, sample group II, and sample group III respectively.
[0091]
[0092]
[0093]
[0094] Step 5: Comprehensive evaluation. Substitute the weight percentages G1, G2, G3 of each sample group calculated in step 2 and the trueness P1, P2, P3 obtained in step 4 into formula (5) to calculate the comprehensive trueness P:
[0095] P=G1·P1+G2·P2+G3·P3=21%×96.8%+42.4%×97.2%+36.6%×98.9%=97.7%
[0096] It is not difficult to see that the comprehensive return to trueness calculated in step 5 satisfies P>97%. According to the return to trueness evaluation standard, the carbon-containing magnesium regenerated particles described in this embodiment can be evaluated to have excellent volume correction effect, and can be directly used as raw materials for regenerated refractory materials.
[0097] In order to verify the reproducibility and reliability of the chemical analysis evaluation method provided in this application, four preliminary samples were randomly selected from the used carbon-containing magnesium regenerated particles described in this embodiment according to the above-mentioned step one method, and repeated tests and calculations were carried out according to steps two to five in sequence, and finally four comprehensive return to truth values P were obtained again (see Table 1).
[0098] Example 2 Evaluation of the Authenticity of Self-produced and Self-collected Used Carbon-containing Magnesium Regenerated Particles without Volume Correction Treatment
[0099] This embodiment is completely consistent with the embodiment 1 in terms of treatment objects, post-use recycling, sorting and other recycling processes, but does not undergo volume correction treatment. Instead, the chemical analysis method is directly used to evaluate the authenticity of the recycled material after the recycling treatment. The specific process is as follows:
[0100] Step 1: Random sampling. According to the procedures and methods specified in GB / T17617-2018 "Rules for Sampling and Inspection of Refractory Raw Materials", the used carbon-containing magnesium regeneration particles are randomly sampled, and sieved through a 0.5mm sieve. The sieve-surface material (particle size ≥ 0.5mm) is taken to obtain the preliminary sample, and the weight of the preliminary sample reaches 500g.
[0101] Step 2: Sample grouping. The preliminary samples extracted in step 1 were manually screened and grouped using mesh sieves with apertures of 1mm and 3mm to obtain sample group I (particle size <1mm), sample group II (1mm≤particle size <3mm), and sample group III (≥3mm). Each sample group was weighed using a weighing device, and the weights were 156g, 220g, and 124g, respectively. The percentage of each sample group in the total weight of the preliminary samples was then calculated. Since the trueness of the used carbon-containing magnesium regenerated particles may be related to the particle size, and most of them are used in the production of regenerated refractory materials in the form of particle size classification, this application will group the samples by particle size, and expects to achieve multi-level detection, comprehensive evaluation, comprehensive understanding, and classified processing.
[0102] Step 3: Group testing. According to GB / T 5069.11 "Chemical analysis methods for magnesium and magnesium-aluminum (aluminum-magnesium) refractories - Determination of calcium oxide and magnesium oxide by complexometric titration", the magnesium oxide contents of sample group I, sample group II, and sample group III obtained in step 2 were measured to be W respectively. 1 MgO =89.64%, W 2 MgO =90.43%, W 3 MgO =91.38%. According to GB / T13245 "Chemical analysis method for carbon-containing refractory materials - combustion weight method for determination of total carbon content", the carbon contents of sample group I, sample group II and sample group III were W 1 C =8.53%, W 2 C =7.92%, W 3 C =6.85%.
[0103] Step 4: Calculate the return truth degree P by group n This embodiment and the embodiment 1 are the same used carbon-containing magnesium refractory materials. The relevant information of the original raw materials in the embodiment 1 is still used here, that is, the magnesium oxide content F in the magnesia sand MgO =97.68%, flake graphite raw material carbon content F C =94.15%, and compare them with the magnesium oxide content (W MgO ) and carbon content (W C ) are substituted into formula (4.1) to calculate the return to truth P1, P2, and P3 of sample group I, sample group II, and sample group III respectively.
[0104]
[0105]
[0106]
[0107] Step 5: Comprehensive evaluation. Substitute the weight percentages G1, G2, G3 of each sample group calculated in step 2 and the trueness P1, P2, P3 obtained in step 4 into formula (5) to calculate the comprehensive trueness P:
[0108] P=G1·P1+G2·P2+G3·P3=31.2%×91%+44%×91.7%+24.8%×92.8%=91.7%. It can be seen that the comprehensive return to trueness calculated in this embodiment satisfies P<95%. According to the evaluation criteria, the used carbon-containing magnesium regenerated particles that have not been subjected to volume correction treatment in this embodiment are evaluated as unqualified in return to trueness. In order to maximize the quality of the used carbon-containing magnesium regenerated materials and improve their recycling rate, it is necessary to subject the used carbon-containing magnesium regenerated particles to volume correction treatment over the entire particle size range (≥0.5mm).
[0109] In order to further verify the reproducibility and reliability of the chemical analysis evaluation method, four preliminary samples were randomly selected again according to the above steps, and repeated tests and calculations were performed on them respectively, and finally four comprehensive return to truth values P were obtained again (see Table 1).
[0110] Example 3 Evaluation of the trueness of the regenerated particles of the purchased used carbon-containing magnesium refractory material after volume correction treatment
[0111] The object of this embodiment is a used carbon-containing magnesium refractory material purchased from the market, and the used carbon-containing magnesium regenerated particles (particle size ≥ 0.5mm) are prepared through recycling, sorting, crushing, screening, and volume correction treatment. There is no reserve sample of the original raw material of the regenerated material, and its related chemical composition information is also unknown. Therefore, in order to quantify the volume correction effect of the object, guide the formulation of volume correction treatment process parameters and evaluate the quality of the used carbon-containing magnesium regenerated particles, this embodiment is suitable for using the volume density detection method to calculate and evaluate its return to trueness, and the specific implementation steps are as follows:
[0112] Step 1: Preparation of reference particles. After the volume correction treatment, first use a sieve to randomly screen the used carbon-containing magnesium regenerated particles (particle size ≥ 0.5mm) for a number of coarse particles (≥ ≥ 4mm), and select the particles with round and full appearance as the reference particle rough selection materials. Then use 320# sandpaper to manually grind and polish the surface of the reference particle rough selection material until the entire surface of the particle emits the luster of magnesium sand crystals, and then the reference particles can be obtained. In this embodiment, the preparation amount of reference particles can reach 300g.
[0113] Step 2: Sample selection. According to the procedures and methods specified in GB / T17617-2018 "Rules for Sampling and Inspection of Refractory Raw Materials", a number of carbon-containing magnesium regeneration and reduction particles (particle size ≥ 0.5 mm) are randomly selected and screened with a sieve with an aperture of 3 mm, and the sieved material is taken to obtain a sample (≥ 3 mm). In this embodiment, the sample weight is 300 g.
[0114] Step 3: Bulk density test. According to GB / T2999-2016 "Test method for bulk density of refractory particles", the bulk density of the reference particles and samples was tested respectively, and the sample bulk density D0 = 3.40g / dm 3 , reference particle volume density D 真 =3.45g / dm 3 .
[0115] Step 4: Calculate the return to truth P. D0 and D 真 Substitute into formula (10) to calculate the return to truth P:
[0116]
[0117] Step 5: Return to Trueness Evaluation: According to the return to trueness P value calculated in step 4, P>97%. Combined with the evaluation criteria, the evaluation opinion that the used carbon-containing magnesium regeneration particles described in this embodiment have excellent volume correction effect is given, and the used carbon-containing magnesium regeneration particles can be directly used as magnesium raw materials for regeneration application.
[0118] In order to verify the reproducibility and reliability of the volume density detection method, this example again prepared 4 reference particles, randomly selected 4 samples, and repeated tests and calculations were performed according to steps 3 and 4, respectively, and finally 4 D0, D 真 And 4 return-to-true values P (see Table 1).
[0119] Example 4 Evaluation of the trueness of the regenerated particles of the purchased used carbon-containing magnesium refractory material without volume correction treatment
[0120] This embodiment is completely consistent with the embodiment 3 in terms of treatment objects, post-use recycling, sorting and other recycling processes, but does not undergo volume correction treatment. Instead, the volume density detection method is directly used to calculate and evaluate the return to trueness of the recycled material after the recycling treatment. The specific process is as follows:
[0121] Step 1: Preparation of reference particles. First, a sieve is used to randomly screen a number of coarse particles (≥4mm) from the used carbon-containing magnesium regeneration particles, and a number of particles with round and full appearance are selected as reference particle rough selection materials. Then, 340# sandpaper is used to manually grind and polish the surface of the reference particle rough selection material until the entire surface of the particle emits the luster of magnesium sand crystals, and then the reference particles (true particles) can be obtained. In this embodiment, the preparation amount of reference particles can reach 300g.
[0122] Step 2: Sample selection: According to the procedures and methods specified in GB / T17617-2018 "Rules for Sampling and Inspection of Refractory Raw Materials", a number of carbon-containing magnesium regenerated particles are randomly selected and sieved with a sieve with an aperture of 3 mm. The sieved material is taken to obtain a sample (≥3 mm). In this embodiment, the sample weight is 300 g.
[0123] Step 3: Bulk density test. According to GB / T2999-2016 "Test method for bulk density of refractory particles", the reference particles prepared in step 1 and the samples selected in step 2 were tested for bulk density, and the sample bulk density D0 = 3.33 g / dm 3 , reference particle volume density D 真 =3.45g / dm 3 .
[0124] Step 4: Calculate the return to truth P. D0 and D 真 Substituting them into formula (10), the return to truth P can be calculated:
[0125]
[0126] Step 5: Return to Trueness Evaluation. According to the return to trueness P value calculated in step 4, P < 95%. Combined with the evaluation criteria, the evaluation opinion that the return to trueness of the used carbon-containing magnesium regenerated particles without volume correction treatment described in this embodiment is unqualified is given. In order to maximize the quality of the used carbon-containing magnesium regenerated materials and increase their recycling rate, they need to be deeply corrected.
[0127] In order to further verify the reproducibility and reliability of the volume density detection method, this example again prepared 4 reference particles, randomly selected 4 samples, and repeated tests and calculations were performed according to step 3 and step 4, and finally 4 D0, D 真 And 4 return-to-true values P (see Table 1).
[0128] Table 1 Test data of each embodiment
[0129]
[0130]
[0131] From Table 1, it can be seen that whether it is the chemical analysis evaluation method or the volume density detection method, as a return to trueness evaluation method, both have good reproducibility and parallelism, and the calculation results are accurate and reliable. By performing repeatability testing, calculation and evaluation of the return to trueness of samples 5 times for each of Example 1, Example 2, Example 3, and Example 4, regardless of whether the carbon-containing magnesium refractory regeneration particles have been subjected to volume correction treatment, the calculation results of the return to trueness of each group show good reproducibility, and the standard deviation between each sample is extremely small, as low as 0.194%, 0.204%, 0.207%, and 0.288%, respectively. The calculation results are accurate and reliable, showing extremely high test evaluation accuracy.
[0132] In order to evaluate the practical guiding significance of the return to trueness evaluation method provided in this application for the application effect of the recycled particles of used carbon-containing magnesia refractory materials, the inventor prepared the same brand of recycled magnesia carbon brick samples by adding the same amount of the same used carbon-containing magnesia refractory recycled particles with different return to trueness, and tested the apparent porosity of each sample after heat treatment at 200℃×24h and the high temperature flexural strength at 1400℃×0.5h according to GB / T2997 "Test Method for Bulk Density, Apparent Porosity and True Porosity of Dense Shaped Refractory Products" and GB / T13473 "Test Method for High Temperature Flexural Strength of Carbon-Containing Refractory Materials". The test results are shown in Table 2. Note: The above national standards without year numbers all refer to their latest versions.
[0133] As can be seen from Table 2, the return to trueness values obtained by the chemical analysis evaluation method and the volume density detection method provided by this application have good guiding significance for predicting the actual performance of carbon-containing magnesia refractory materials after use. It is not difficult to see from the table that whether the return to trueness is tested by means of the chemical analysis evaluation method or the volume density detection method, as the return to trueness continues to increase, the carbon-containing magnesia regenerated particles after use are closer to the original particle morphology, and the apparent porosity of the regenerated bricks produced and prepared by them shows a continuous decrease as a whole, and the high-temperature flexural strength continues to increase. The law of change, thereby establishing a corresponding relationship between the return to trueness index of the regenerated particles and the key performance indicators of actual regeneration applications. Therefore, the return to trueness and its test and evaluation method provided by this application have good guiding and reference value for the quality assessment of carbon-containing magnesia regenerated particles after use and the prediction of the effect of regeneration application!
[0134] Table 2 Key performance indicators of recycled bricks prepared by adding recycled materials with different fidelity in the same proportion
[0135]
[0136]
Claims
1. A method for evaluating the authenticity of recycled particles of used carbon-containing magnesia refractory materials, characterized in that The following steps are involved: The used carbon-containing magnesium regeneration particles include magnesium sand particles and an outer graphite carbon layer; the return to trueness can be quantified as the percentage of the weight of magnesium sand particles to the weight of the entire used carbon-containing magnesium regeneration particles, and the calculation formula is as follows: Formula (1) In the formula, W 1 is the mass of magnesia particles in the carbon-containing magnesium regeneration particles after use, W 2 is the quality of the graphite carbon layer, and P is the degree of return to trueness for evaluating the reprocessing process; Evaluation criteria: P <95%, the carbon-containing magnesium regeneration particles after use are unqualified in terms of trueness index, and further deep correction treatment or scrapping is required; if 95%≤ P <97%, the return to truth can be judged as qualified, but the used carbon-containing magnesium regeneration particles should be downgraded or properly re-adjusted; if P ≥97%, with excellent return to truth index, the carbon-containing magnesium regeneration particles can be used directly after use; There are two sources of the spent carbon-containing magnesium regeneration particles. One is self-production and self-collection. The chemical composition of the original raw materials is completely known, and samples are stored for reference. Chemical analysis can be performed at any time. The chemical analysis evaluation method can be used to evaluate the return of truth, that is, the magnesium oxide content in the spent carbon-containing magnesium regeneration particles is detected by chemical analysis. W MgO and carbon content W C , and combined with the magnesium oxide content in the original magnesia raw material F MgO , Carbon content in original graphite raw material F C , it can be concluded that they are W 1. W 2, and then substitute it into formula (1) to get the calculation formula of the return to truth P based on the chemical analysis evaluation method; the other is to purchase from the market, whose original raw material information is unknown and there is no sample for reference. It is necessary to first prepare the reference particles by manually grinding the used carbon-containing magnesium regenerated particles. For this, the volume density test method should be used to evaluate the return to truth, that is, the volume density of the used carbon-containing magnesium regenerated particles and the reference particles is tested, and the volume density value is derived and calculated. W 1. W 2, and substitute it into formula (1) to obtain the calculation formula of the return truth degree P based on the volume density detection method.
2. The method for evaluating the trueness of recycled particles of used carbon-containing magnesia refractory materials according to claim 1, characterized in that: The chemical analysis method includes the following steps: Step 1, random sampling: randomly select the used carbon-containing magnesium regeneration particles with a particle size of ≥0.5 mm, with a total amount of 500 g to obtain a preliminary sample; Step 2, sample grouping: Use mesh sieves with apertures of 1 mm and 3 mm to manually screen and group the preliminary selected samples extracted in step 1 to obtain sample group I with particle size <1 mm, sample group II with particle size 1 mm≤<3 mm, and sample group III with particle size ≥3 mm. Use weighing equipment to weigh each sample group and calculate its percentage G1, G2, and G3 of the total weight of the preliminary selected samples; Step 3: Group testing: Use existing testing methods to measure the magnesium oxide content of sample group I, sample group II and sample group III obtained in step 2. W MgO and carbon content W C ; Step 4: Calculate the return to truth by group P n : Query and obtain the original raw material information of the used carbon-containing magnesium regeneration particles, and calculate the magnesium oxide content in the original magnesium sand raw material. F MgO and the carbon content in the original graphite raw material F C The magnesium oxide content of each sample group measured in step 3 W MgO and carbon content W C Substituting them into formula (4.1) for calculation, the return to truth of sample group I, sample group II and sample group III can be calculated respectively. P 1. P 2. P 3; Formula (4.1) In the formula, P n is the return to truth of sample group n, is the magnesium oxide content of sample group n, is the carbon content of sample group n; Step 5: Comprehensive evaluation: The weight percentage of each sample group calculated in step 2 and the degree of return to truth of each sample group obtained in step 4 are calculated. P 1. P 2. P Substitute 3 into formula (5) to calculate the comprehensive return to truth P ; Formula (5) In the formula, G1, G2, and G3 are the percentages of each sample group in the total amount of the preliminary selected samples, and their total amount should be 100%, that is, .
3. The method for evaluating the trueness of recycled particles of used carbon-containing magnesia refractory materials according to claim 1, characterized in that: The bulk density test method includes the following steps: Step 1, preparation of reference particles: first, a sieve is used to randomly screen a number of coarse particles with a particle size of ≥4mm from the used carbon-containing magnesium recycled particles, and a number of round and full particles are selected from them to obtain reference particle rough selection materials; then, 320# or higher sandpaper is used to manually grind and polish the surface of the reference particle rough selection materials until the entire surface of the particles emits a magnesium sand crystal luster, and the reference particles are obtained; the weight of the obtained reference particles is 300g; Step 2, sample selection: randomly select a number of used carbon-containing magnesium regeneration particles, and screen them with a sieve with a pore size of 3 mm, and take the sieve to obtain a sample; the weight of the selected sample is 300g; Step 3: Perform volume density tests on the reference particles and samples respectively to obtain the volume density of the reference particles. D 真 and the bulk density of the sample D 0; Step 4: Calculate the return to truth P :Then the test result in step 3 is D 0. D 真 Substitute into formula (10) to calculate the return to truth P; Formula (10).